2002
DOI: 10.1016/s1074-5521(02)00130-8
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of an Abasic Hairpin Ribozyme by Cationic Nucleobases

Abstract: The hairpin ribozyme catalyzes a reversible phosphodiester cleavage reaction. We examined the roles of conserved nucleobases in catalysis using an abasic ribozyme rescue strategy. Loss of the active site G8 nucleobase reduced the cleavage rate constant by 350-fold while loss of A9 and A10 nucleobases reduced activity less than 10-fold. Certain heterocyclic amines restored partial activity when provided in solution to the variant lacking G8. Heterocyclic amines that were capable of rescue shared the exocyclic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
97
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 49 publications
10
97
1
Order By: Relevance
“…Water was not observed in the active site of previous 4WJ hairpin ribozyme structures, although solvent has been invoked to account for both structural and biochemical observations regarding the mechanism of action (10,(15)(16)(17). In earlier structural studies, it was noted that the N1 imino position of G8 appeared to function as an obligate proton donor to the 2'-oxygen of the nucleophile, and not as a proton acceptor as corroborated here for AP8 and DAP8.…”
Section: Implications For Water In the Active Sitementioning
confidence: 57%
See 2 more Smart Citations
“…Water was not observed in the active site of previous 4WJ hairpin ribozyme structures, although solvent has been invoked to account for both structural and biochemical observations regarding the mechanism of action (10,(15)(16)(17). In earlier structural studies, it was noted that the N1 imino position of G8 appeared to function as an obligate proton donor to the 2'-oxygen of the nucleophile, and not as a proton acceptor as corroborated here for AP8 and DAP8.…”
Section: Implications For Water In the Active Sitementioning
confidence: 57%
“…The first entails acid/base catalysis involving G8 and/or A38 (14,23,52). The second calls for electrostatic stabilization involving localized nucleobase charge dissipation (15)(16)(17)23,53). Although X-ray crystallography cannot differentiate between these proposals, it can provide additional stereochemical information relevant to understanding the principles by which the enzyme promotes catalytically productive or non-productive states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleobase could stabilize the reaction transition state by specific hydrogen bonding, or a protonated adenine might stabilize the dianionic phosphorane electrostatically. Both effects have been proposed for the hairpin ribozyme (3,21). Were this to be the case in the VS ribozyme, then substitution of the nucleobase at position 756 could lead to lower cleavage rates, as observed.…”
Section: Discussionmentioning
confidence: 75%
“…However, recent crystallographic and biochemical experiments have suggested that only two nucleobases in the ribozyme, G8 and A38, are directly involved in reaction chemistry ( Fig. 1 A) (9)(10)(11)(12). An open question is therefore how all of the other functional groups exert their influence on activity.…”
mentioning
confidence: 99%